(untitled) (Journal of the College of Education for Women, 2019)
The notion of presupposition and its triggers have been studied by many scholars,linguists and philosophers, but as far as the researcher knows, the investigation ofpresupposition triggers in journalistic texts has not been explored yet. Therefore, thepresent research tries to identify the main presupposition triggers used in Englishjournalistic texts. It is hypothesized that there are many presupposition triggers inEnglish journalistic texts. The steps to be followed in this study are exploring theconcept of presupposition, investigating the semantic and pragmatic presupposition,and identifying the presupposition triggers used in the English journalistic textsaccording to a model proposed by the researcher based on Karttunen (n.d.), cited inLevinson 1983:181-184, and Yule 1996: 28.The study is designed to the presupposition triggers of six randomly selectedEnglish journalistic texts. These texts have been sampled from six different nationaland regional English newspapers representing a range of political and regionaldifferences.